Study of cutaneous malignancy and various reconstructive techniques in a tertiary care center of West Bengal, India - Dibyendu Das; Alladi SJ Swaroop; Passang Rai (Asian Journal of Medical Sciences)
Background: Skin cancer can be categorized into cutaneous melanoma and non-melanoma skin cancer (NMSC). Common NMSC is basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). Surgical reconstruction following excision of skin cancer is an essential part of treatment plan.